História da Matemática no ensino fundamental : usos em sala de aula pelo professor de matemática da rede municipal de Aracaju/SE - Guimarães, Marcos Denilson (2011)
This article presents the results of a survey whose aim was to identify whether or how the Mathematics teachers of municipal schools in Aracaju make use of the History of Mathematics to deal with mathematical contents on the final years of Junior High School. In order to accomplish such a task, first it was identified the subjects through the intersection between the names of the students who attended the subject History of Education at Universidade Federal de Sergipe - UFS, and the names of the teachers who had taught at municipal schools in 2010. From a quantity of 37 students who met the above criteria, 19 semi structured interviews were made with the group. In addition, two professors of the subject History of Mathematics, offered for the graduates in Mathematics at UFS, were also interviewed. In this case, the aim was to identify the historical contents presented in the course plans in an attempt to establish the same theoretical bases in relation to the contents and the way how they were studied by the teachers of the municipal schools in Aracaju. As theoretical foundation, it was adopted the authors: Fauvel (1997) to differentiate between history of mathematics written with initial capitals and lower case with initial Feliciano (2008), Miguel (1997), Miguel e Miorim (2008) about the uses of history of mathematics in the classroom e Valente (2007) to the treatment of sources. Based on the data collected, it is possible to affirm that most teachers use the History of Mathematics in the classroom. In relation to how, the most frequent use is the History of Mathematics as teaching resources, tied to the use as motivation, as curiosity, as explanation of the why. In these cases, the main role performed by the teacher is to present the contents and the historical information. The confirmation of this is in the verbs used, such as: to count, to explain and to cite, considered as indicative that the teachers adopt the model of lecture and the historical information as a form of explaining some why, which contributed to the students to become not only listeners in face of the knowledge which are passed on them. The result of this survey is an indicative that as soon as possible, it should be made an investment on other surveys in order to experiment the use of the History of Mathematics as a teaching methodology in which the historical information is the starting point to teach mathematical contents.